Length (L): w + 3       ⇒2(w + 3)
width (w): w           ⇒ w - 1
Area (A) = L x w
     A = (w + 3)(w)
     A = w² + 3w
*******************************************
    A + 176 = 2(w + 3)(w - 1)
(w² + 3w) + 176 = 2(w + 3)(w - 1)
w² + 3w + 176 = 2w² + 4w - 6
    3w + 176 = w² + 4w - 6
         176 = w² + w - 6     Â
          0 = w² + w - 182
          0 = (w - 13) (w + 14)
0 = w - 13 Â Â Â Â Â Â 0 = w + 14
w = 13 Â Â Â Â Â Â Â Â Â w = -14
Since width cannot be negative, disregard -14
w = 13
Length (L): w + 3 Â = (13) + 3 Â = 16
Answer: width = 13 in, length = 16 in